Detection of Fast Radio Transients with Multiple Stations: A Case Study Using the Very Long Baseline Array - Thompson, D.; Wagstaff, K.; Brisken, W.; Deller, A.; Majid, W.; Tingay, Steven; Wayth, Randall (Institute of Physics Publishing, Inc., 2011)
Recent investigations reveal an important new class of transient radio phenomena that occur on submillisecond timescales. Often, transient surveys’ data volumes are too large to archive exhaustively. Instead, an online automatic system must excise impulsive interference and detect candidate events in real time. This work presents a case study using data from multiple geographically distributed stations to perform simultaneous interference excision and transient detection. We present several algorithms that incorporate dedispersed data from multiple sites, and report experiments with a commensal real-time transient detection system on the Very Long Baseline Array. We test the system using observations of pulsar B0329+54. The multiple-station algorithms enhanced sensitivity for detection of individual pulses. These strategies could improve detection performance for a future generation of geographically distributed arrays such as the Australian Square Kilometre Array Pathfinder and the Square Kilometre Array.